Implementasi Strategi Pengembangan Industri Kelapa Sawit dalam Menghadapi Revolusi 4.0 - Miftahulk N.A Buluaro; Putra Jaya Sinulingga; Riki Rikardo Simanjuntak; Kristian Jonathan Harianja; Wahyu Hutapea; Andreas S.M Raja Guk Guk; Rizky Pratama Putra Damanik (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
This research uses a qualitative descriptive method to evaluate the implementation of development strategies in the palm oil industry in facing the Fourth Industrial Revolution. The palm oil industry is a nationally strategic sector that plays a crucial role in Indonesia’s economy, both in terms of exports and employment absorption. In the digital era, technological transformation has become a necessity for industry players to improve efficiency, transparency, and global competitiveness. This study examines various adaptive strategies that have been developed, such as the application of digital technologies in the supply chain, integration of information systems in production processes, and the strengthening of human resources through technology-based training. The analysis is conducted through a literature review of recent academic works, government policies, and industrial reports. The findings indicate that the implementation of digitalization strategies still faces challenges, such as limited technological infrastructure, disparities in digital literacy, and regulations that are not yet fully supportive. These results provide a comprehensive picture of the readiness and direction of the palm oil industry’s development in the Industrial Revolution 4.0 era to achieve long-term sustainability and efficiency.